PENGARUH DISIPLIN KERJA, REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN PT GENERASI MUDA TEHNIK RIAU PEKANBARU - ,Ahmad Rifqi, Yulisandri Maulidya ,Marzolina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the effect of work discipline, reward and punishment on employee performance. The population in this study were prepaid employees of PT Generasi Muda Tehnik Riau, which totaled 47 employees. The analytical method used is multiple linear regression analysis. The results based on the partial t test show that work discipline has an effect on employee performance with a tcount of 3.507 and a significance of 0.001, rewards affect employee performance with a tcount value of 3.019 and a significance of 0.004, punishment has an effect on employee performance with a tcount value of 2.473 and a significance of 0.017. Furthermore, based on the simultaneous F test, it shows that work discipline, reward, and punishment jointly affect employee performance with an F count of 17.113 and a significance of 0.000. Keywords: Work Discipline, Reward, Punishment and Employee Performance